2010
DOI: 10.1258/ebm.2009.009151
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the hypothesis that 10-formyldihydrofolate is the in vivo substrate for aminoimidazolecarboxamide ribotide transformylase

Abstract: We postulate that 10-formyl-7,8-dihydrofolate (10-HCO-H(2)folate), not 10-formyl-5,6,7,8-tetrahydrofolate (10-HCO-H(4)folate), is the predominant in vivo substrate for mammalian aminoimidazolecarboxamide ribotide (AICAR) transformylase, an enzyme in purine nucleotide biosynthesis de novo, which introduces carbon 2 (C(2)) into the purine ring. 10-HCO-H(2)folate exists in vivo as labeled 10-formyl-folic acid (10-HCO-folic acid: an oxidation product of 10-HCO-H(4)folate and 10-HCO-H(2)folate) and is found after d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The importance of adenosine as an anti-inflammatory mediator was questioned 53 , 54 and could not been convincingly demonstrated in later experiments 55 . It is, however, generally accepted that AICAR (ZMP) increases after methotrexate 56 —either by direct inhibition of AICART or alternatively, favoring the reverse reaction by increasing dihydrofolate via blockade of dihydrofolate reductase 52 . (For more details, see the legend of Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of adenosine as an anti-inflammatory mediator was questioned 53 , 54 and could not been convincingly demonstrated in later experiments 55 . It is, however, generally accepted that AICAR (ZMP) increases after methotrexate 56 —either by direct inhibition of AICART or alternatively, favoring the reverse reaction by increasing dihydrofolate via blockade of dihydrofolate reductase 52 . (For more details, see the legend of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These are based on the reversibility of the reaction (indicated by the double-headed arrow) and that AICART has rather low affinity for the polyglutamates. As an exception to all other reactions in mammalian one-carbon metabolism 51 10-formyl-7, 8-dihydrofolate and dihydrofolate can be substrate and product, respectively 52 . Increase of the product by blockade of the dihydrofolate reductase will slow the reaction and lead to increase in AICAR.…”
Section: Resultsmentioning
confidence: 99%
“…The authors hypothesized that it could be due to the differential binding mechanisms of the substrates to the enzymes: GART can bind its two substrates in a random manner (27), whereas ATIC obeys an ordered sequential binding mechanism, with 10-formyltetrahydrofolate binding first before ZMP can bind (28). Alternatively, it has been reported that human ATIC and GART do not utilize the same 10-formyltetrahydrofolate pool (29,30). Thus, ATIC can use 10-formyltetrahydrofolate formed from tetrahydrofolate and histidine or formate, whereas GAR transformylase, which is in a complex with the trifunctional folate-metabolizing enzyme, can use 10-formyltetrahydrofolate formed from tetrahydrofolate and glycine or serine.…”
Section: Discussionmentioning
confidence: 99%
“…as a substrate in vitro (8,9); 3) the unnatural isomer, [6R]-5-formyltetrahydrofolate (5-formyl-H 4 folate), is inactive as a substrate for folate-metabolizing enzymes in vitro but bioactive in vivo in humans, suggesting its conversion to 10-formyl-H 2 folate in vivo (10); and 4) the kinetics of C 2 and C 8 enrichment of uric acid in humans by [6RS]5-13 C-formyl-H 4 folate are different, suggesting that GAR and AICAR transformylases do not utilize the same 10-formyl-H 4 folate pool (9). In this review, we discuss the distribution of onecarbon from ring-2-C of histidine, 2-C of glycine, 3-C of serine, and formate to C 2 and/or C 8 of uric acid as well as other purines.…”
Section: Introductionmentioning
confidence: 99%